The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.5222/tp.2021.29392
|View full text |Cite
|
Sign up to set email alerts
|

Ventriculo-Peritoneal Shunt Infections in a Tertiary Center, 3 Years Experience

Abstract: INTRODUCTION: Ventriculo-peritoneal shunt infection is the most important complication of shunt applications. In pediatric age, shunt infections are associated with shunt dysfunction, requirement for shunt revision, neurodevelopmental delay, prolonged hospital stay, and high treatment costs. In this study, we aimed to evaluate the characteristics of shunt infections of our patients and to compare the differences between early and late infections, infections caused by staphylococci and other strains and infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Previous studies have stated that the most common bacteria causing meningitis in the use of a VP shunt is Staphylococcus bacteria [16]. Despite advances in surgical techniques and infection control, infections associated with VP shunt placement still range from 5 to 18% and are mostly caused by gram-positive bacteria (59%) [17]. This is in accordance with the results of a study which found that 24% of samples with the use of a VP shunt and the most common cause were gram-positive bacteria, namely Staphylococcus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have stated that the most common bacteria causing meningitis in the use of a VP shunt is Staphylococcus bacteria [16]. Despite advances in surgical techniques and infection control, infections associated with VP shunt placement still range from 5 to 18% and are mostly caused by gram-positive bacteria (59%) [17]. This is in accordance with the results of a study which found that 24% of samples with the use of a VP shunt and the most common cause were gram-positive bacteria, namely Staphylococcus sp.…”
Section: Discussionmentioning
confidence: 99%
“…∼26,000 TRY [30] Cardiac implantable electronic devices ∼1.2-3.6% [31] Staphylococcus aureus (MSSA and MRSA), Staphylococcus epidermidis (MSSE and MRSE), other CoNS, other Grampositive cocci, GNB, Candida and Aspergillus (fungi) [32] . Intervention [33]: Removal of all CIED hardware and prolonged intravenous antibiotics…”
Section: Introductionmentioning
confidence: 99%